Nations before the Nation-State between city-state and empire from antiquity to the present - Schön, Anna Marisa ca. 20./21. Jh (Cambridge University Press, 2024)
Throughout Antiquity and the Middle Ages, thinkers understood nations as communities defined by common language, culture, and descent, and sharing strong bonds of belonging and solidarity. Even so, they did not assume that nations would also be appropriate units of government. The recovery of this historical understanding, in turn, yields valuable insights for contemporary political dilemmas. Nations Before the Nation-State offers the first extended study of the idea of the nation in ancient and medieval political thought. It recovers a pre-modern conception of the nation as a cultural and linguistic community, rather than a political association, and examines better means for thinking about nationhood. Offering a historic perspective from which to address challenges of nationalism, this book engages with debates on multiculturalism, liberal nationalism, and constitutional patriotism and argues that contemporary political dilemmas can be resolved more organically by recovering modes of thinking that have resolved similar tensions for centuries